Working in the Global Economy : How to Develop and Manage Your Career Across Borders. - Simeon, Roblyn (Taylor and Francis, 2012)
It is clear that although the human resource management field has been drastically affected by global competition over the last twenty years, most of the research and publications in the field are geared to providing corporations with an understanding of their business environment. This book takes an entirely different approach by looking at the job and career markets from the point of view of individuals who are searching for new strategies to find, develop and manage their careers in a global environment. Not only does it provide the individual with the tools necessary to evaluate various do.